Composite mechanical deformation based semi-analytical prediction model for dynamic loaded contact pressure of thin-walled aerospace spiral bevel gears. (February 2022) - Lu, Shaofan; Ding, Han; Rong, Kaibin; Rong, Shifeng; Tang, Jinyuan; Xing, Bin
Abstract: An innovative semi-analytical prediction model for dynamic loaded contact pressure is proposed for thin-walled aerospace spiral bevel gear transmission under both high speed and heavy load conditions. To distinguish with the traditional rotor dynamic analysis focusing on vibration effect for global system, a new dynamic loaded tooth contact analysis (DLTCA) focusing on loaded contact effect for local contact area is developed. In particular, for thin-walled gear structure including tooth flank, web, hub and supporting shaft, its composite mechanical deformation in forms of bending, shearing, torsion and other combinations are introduced into DLTCA solution for prediction. Firstly, considering tooth flank flexural behaviors, tooth flank simulation and finite element modeling is developed by using universal motion concept (UMC) machine settings. Then, for different deformation types at different parts of gear structure, the accurate composite mechanical deformations are determined for tooth flank, web, hub and supporting shaft, respectively. Moreover, DLTCA considering composite mechanical deformations is performed to get a semi-analytical prediction model for dynamic loaded contact pressure having systematically time-varying characteristics. Finally, the given numerical instance is provided to verify the proposed method. Highlights: Data-driven spiral bevel gear modeling using universal motion concept (UMC) machine settings. Composite mechanical deformation solution for aerospace spiral bevel structure. Dynamic loaded tooth contact analysis (DLTCA) considering composite mechanical deformation. Data-driven analytical prediction to dynamic loaded contact pressure and its distribution.